A clinico-pathological study of patients with thyroid swelling and their management in a tertiary care centre in western Uttar Pradesh - Tyagi, Mohini; Chatterjee, Probal (Asian Journal of Medical Sciences, 2021)
Background: Thyroid diseases are common worldwide and in India too there is a significant burden of thyroid disease. Thyroid disease has a reported prevalence of 4-7% in the general population on neck palpation and in autopsy series it may be as high as 50% if subclinical nodules are included. The clinical presentation of thyroid swellings can be very misleading and a definitive diagnosis cannot be done without proper investigations. Aims: To conduct a clinic-pathological study of thyroid swellings along with their management in a tertiary care center. Objectives: 1. To study the various clinical presentations of thyroid swellings 2. To record the FNAC findings in each case. 3. To perform histopathological examination of all operative specimens and compare the results with preoperative diagnosis. Materials and Methods: A one-year prospective study was done in which 50 patients with thyroid swelling were identified. Detailed information regarding all relevant parameters was recorded and treatment was done as per standard protocol. Results: Female preponderance of cases was seen (3.16:1). Maximum cases were in 36-45 year age group and 70% cases were premenopausal females. Multinodular goiter was commonest clinical presentation and colloid goiter was most common FNAC finding. Hemithyroidectomy was the most frequently performed operation. Final results showed that colloid goiter was the most commonly diagnosed benign condition while papillary carcinoma was the commonest malignancy. Conclusion: Most studies show female preponderance of cases. Multinodular goiter is the commonest clinical presentation world-wide. Colloid goiter is the most commonly diagnosed cause of thyroid swelling. Though FNAC is not 100% accurate, it has an important role in the initial evaluation of these patients. Histopathogical examination of specimen is the gold-standard investigation for final diagnosis. Due to the risk of an underlying malignancy, a proper evaluation of thyroid swellings is a must as they have excellent cure rate if treated early.